Books (Res Medica, 2014)
• New Aspects of Human Genetics. British Medical Bulletin, January 1969.• Tile Eye in General Practice (5th. Edition) by C.R. S. Jackson. E. & S. Livingstone Ltd. 30/-.• Recent Advances in Pharmacology (4th. Edition).Edited by Robson & Stacey. J. & A. Churchill,• London.• Body Fluids in Surgery (3rd. Edition) by J. Wilkinson. E. & S. Livingstone Ltd.• The Logic of Medicine by D. A. K.  Black. Oliver & Boyd Ltd. 7/6d.• A Manual of English for Overseas Doctors by Joy E. Parkinson. E. & S. Livingstone Ltd.